Exploring the transformative potential of collaborative art projects on the Stellenbosch University campus - Perold, Karolien; Costandius, Elmarie (South African Journal of Higher Education, 2016)
The potential of visual art projects in negotiating social transformation within the context of a South African higher education institution is explored in this article. The experiences of students and staff involved in three collaborative visual art projects initiated on the Stellenbosch University campus during 2013 to 2014 was explored through interviews, observations and reflective writing. It was found that through harnessing the medium of art as critical dialogic tool operating amidst the embedded differences and divides of the past, institutional culture can be re-imagined and aspects of critical citizenship, particularly tolerance of difference and democracy, can be realised within the collective university community. In conclusion, it is suggested that visual art projects of this kind seem to have the potential to access what Homi Bhabha terms ‘Third Space’ and to facilitate transformative learning. It can play a valuable part in negotiating social transformation in South African higher education.